One-way energy absorption in OWC chambers – passive vs. active venting (Proceedings of the European Wave and Tidal Energy Conference, 2025)
In this paper we report on some recent progress towards understanding and optimizing the energy production from Oscillating Water Column (OWC) chambers for Wave Energy Converters (WECs). This work is part of the DTU OWC validation test case under the OES Task 10 on numerical modelling initiate by the OES international technology programme for collaboration on Ocean Energy Systems under the IEA https://www.ocean-energy-systems.org/oes-projects/wave-energy-converters-modelling-verification-and-validation/.  In particular, we are interested in comparing the performance of one-way vs. two-way energy absorption strategies. Conventional two-way absorption relies on a Wells or self-rectifying air turbine that spins in the same direction on both the inhale and the exhale half-cycles. For one-way extraction, the chamber is opened to the atmosphere on one half-cycle and air is forced through the turbine on the other half-cycle, allowing for a more efficient unidirectional air turbine. Numerical calculations predict that, near resonance, as much (or even more) energy can be extracted using the one-way strategy. Preliminary experimental measurements using a crude passive valve system show the reverse however, with significantly less energy absorbed by the one-way strategy. An obvious loss of energy due to the passive valve is apparent from the measurements, so we are working on an active valve system to remove these losses. The paper and presentation will describe our calculations using weakly-nonlinear potential flow theory along with our previous and current experimental campaigns using a single fixed OWC chamber. The model is quite small with an internal horizontal chamber area of 10 by 12cm, so air compressibility effects are negligible. It is fixed to one wall of the wave flume in the hydraulics laboratory at the Technical University of Denmark (DTU) which is 25m long by 0.6m wide with a water depth of 0.65m. We test in regular waves of periods from 0.57 to 1.64s and two steepness values of H/L=0.025 and 0.04 where H is the wave height and L is the wave length. The air turbine is modelled by an orifice plate with a diameter of 0.016m corresponding to about 1.7% of the chamber surface area. This is a good model of an impulse turbine. Two wave probes measure the internal chamber surface level and the pressure relative to atmospheric is measured by one pressure probe. The absorbed power can be computed from these measurements in several ways by invoking the pressure-flux relationship across the orifice. Experimental and numerical results are compared using two-way, up-stroke and down-stroke absorption strategies. We discuss issues related to the accuracy of the measurements, the control of the active venting valve and challenges associated with numerical modelling of this seemingly simple OWC test case.